Why Does Organizational Citizenship Behaviour Affect The Organizational Sustainability Performance Of Msmes With The Role Individual Work Behaviour? - saryadi, saryadi; Purnomo, Singgih; Hastuti, Indra; Sentosa, Ilham (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
A person's behavioural condition will affect the continuity of work and activity. This study seeks to understand how organizational citizenship behaviour will affect the organizational sustainability performance of MSMEs with the role of individual work behaviour directly or indirectly. Research with sample of 266 MSMEs is considered sufficient in a study. Data analysis is carried out through data quality tests, path analysis, statistical tests and determination coefficients equipped with Sobel tests. The results in this study show that 1) organizational citizen behaviour has a positive significant effect on individual work behaviour; 2) organizational citizen behaviour has a positive significant effect on organizational sustainability performance; 3) individual work behaviour has a positive significant effect on organizational sustainability performance; 4) individual work behaviour as an intervening of affect organizational citizen behaviour influence on organizational sustainability performance; 5) the indirect influence of organizational citizen behaviour on organizational sustainability performance through individual work behaviour is more effective than the direct influence. 6) total determination coefficient value= 0.8206. this means that 82.06% of the organizational citizen behaviour variable affects organizational sustainability performance with individual work behaviour as an intervening. other factors outside the model influence the remaining 17.94%.